Comparison of anterior and posterior approaches in Treating odontoid fractures: a meta-analysis and systematic review - Bao, Xianguo; Chen, Yingjun; Guo, Chen; Xu, Shuai (Frontiers in Surgery, 2023)
Background: Odontoid fracture has accounted for 15% to 20% of cervical injury. Although the operation methods various in different types, the superiority of overall outcomes of anterior approach (AA) and posterior approach (PA) in the treatment of odontoid fracture was still of controversy. Thus, a meta analysis was performed on comparison of AA and PA for this group. Methods: The relevant studies were searched in PUBMED/Medline, Cochrane library, EMBASE, China Biological Medicine (CBM) and Wanfang database from the onset of conception to June 2022. Prospective or retrospective comparative study of AA and PA on odontoid fractures was screened, referring to fusion rates (primary outcomes), complications and postoperative mortality. Meta-analysis on the primary outcomes and systematic review for other outcomes were performed, the procedure was conducted with Review Manager 5.3. Results: There were 12 articles with 452 patients included, all publications were retrospective cohort study. The average postoperative fusion rate was respectively (77.5 ± 17.9) % and (91.4 ± 13.5) % in AA and PA, with statistical significance (OR=0.42[0.22, 0.80], P=0.009). Subgroup analysis showed there was difference on fusion rate between AA and PA in the old group (OR=0.16[0.05, 0.49], P=0.001). There are five articles referred to postoperative mortality and the rate between AA (5.0%) and PA(2.3%) showed no statistical difference (P=0.148). There were 9 studies referred to complications with a rate of 9.7%. The incidence of complications in AA and PA group was comparable (P=0.338) and the incidence of non-fusion and complications was irrelevant. The most cause of death was myocardial infarction. The time and segmental movement retention of AA were possibly superior to PA. Conclusion: AA may be superior on the operation time and motion retention. There were no difference in complications and mortality between the two approaches. The posterior approach would be preferred on fusion rate.